LISA 2020: Promoting Statistical Practice and Collaboration in Developing Countries1 - Vance, Eric A.; Love, Kim; Awe, O. Olawale; Pruitt, Tonya R. (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
A network of statistics and data science collaboration laboratories ("stat labs") can multiply the impact of its constituent stat labs. Networks facilitate mentorship between network members, enable exchanges, share best practices, provide purpose and motivation to other members, and yield increased opportunities for all members. In this chapter, we describe the history, key events, current state, and future directions of the LISA 2020 program, which is centered at the Laboratory for Interdisciplinary Statistical Analysis (LISA) at the University of Colorado Boulder, United States. With roots as far back as 1948, LISA 2020 began in 2012 and achieved its initial goal of creating a network of at least 20 stat labs in developing countries by the year 2020. Currently comprised of 35 full member stat labs in 10 countries and 13 additional proposed or transitional stat labs, the LISA 2020 Network is well positioned to deliver on its current objectives to help create new stat labs, build their capacity to become strong and sustainable, enable and accelerate their transforming of evidence into action for development, and publicize their inevitable successes in applying statistics and data science to positively impact humanity.